Barriers and incentives for mobility in a bike-sharing system in a Spanish municipality - Sanmiguel-Rodríguez, Alberto (2023)
Introduction: Interest in urban cycling is increasing and the number of shared bike programs has grown rapidly in recent years. Therefore, the objective that is intended to be achieved in this study is to know if factors such as seasons, routes and altitudes affect the use of the shared bicycle system in a Spanish municipality. Methods: A quantitative and longitudinal study has been designed with the collection and analysis of data from the BSS of Vilagarcía de Arousa, registering a total of 84,183 observations (men n = 59,159; women n = 25,024). The data extracted from the system was collected and statistically analyzed through the IBM SPSS version 21.0 program. A significance value of p < 0.05 has been established. Results: The most used station was the one located in the center of the city, representing a total of 39% of the observations. The neutral elevation, that is, leaving a station and depositing the bicycle in another with the same altitude, represented 65.5% of the total records. Conclusions: The municipality of Vilagarcía de Arousa has some favorable topographical characteristics to be a profitable service that promotes healthy habits as a means of active transportation in the urban environment, as well as an improvement in urban mobility and a less polluted environment.